Nelson handwriting book 1 - Smith, Both in the Mathematics Department Peter (Thomas Nelson Publishers, 2000)
Clearly laid out pages help pupils work independently The 'Getting ready to write' page at the front of each book enables pupils to check that they are ready to begin writing The 'Check your writing' page at the back of each book enables pupils to check their own progress